Answer:
Answer is x+y-3=0
Step-by-step explanation:
[tex]given \\ passing \: through(4, - 1) \\ given \: equation \: is \: perpendicular \: to \: y = x + 2 \\ x - y + 2 = 0 \\ slope \: of \: the \: equation = 1 \\ when \: it \: is \: perpendicular \: slope \: becomes \: - 1 \\ the \: equation \: is \\ y - y1 = m(x - x1) \\ x1 = 4 \: \: \: \: y1 = - 1 \: \: \: \: \: \: m = - 1 \\ o n \: substituting \: the \: values \\ y + 1 = - 1(x - 4) \\ y + 1 = - x + 4 \\ x + y - 3 = 0[/tex]
HAVE A NICE DAY!
THANKS FOR GIVING ME THE OPPORTUNITY TO ANSWER YOUR QUESTION.